Sur les spécificités discursives de (be) likely - Grégory Furmaniak (Lexis: Journal in English Lexicology)
This paper aims to characterize the textual properties of the modal adjective likely, which has been largely neglected in the literature on modal studies. Our quantitative and qualitative analysis is based on a corpus stratified into seven discourse modes and has helped us to identify three distinct uses of the modal form under study. Each of these uses is associated with specific semantic, syntactic, argumentative and registral features. However, the study also shows that a number of properties are common to all the uses of likely, the most remarkable ones being the adjective’s strong attraction towards existential processes, future-time reference and logical coherence links, especially cause/consequence relations.